Molecular Mechanisms and Drug Development in Aquaporin Water Channel Diseases: Molecular Mechanism of Water Channel Aquaporin-2 Trafficking - Yumi Noda; Sei Sasaki (Elsevier, 2004)
Targeted positioning of water channel aquaporin-2 (AQP2) strictly regulates body water homeostasis. Trafficking of AQP2 to the apical membrane is critical for the reabsorption of water in renal collecting ducts. Besides the cAMP-mediated effect of vasopressin on AQP2 trafficking to the apical membrane, other signaling cascades also induce this sorting. Recently, AQP2-binding proteins that directly regulate this trafficking have been uncovered: SPA-1, a GTPase-activating protein (GAP) for Rap1, and cytoskeletal protein actin. This review summarizes recent advances related to the trafficking mechanism of AQP2 and its defect causing nephrogenic diabetes insipidus (NDI). Keywords:: aquaporin-2, PKA phosphorylation, missorting, Rho, cytoskeleton